PENGARUH METODE PEMBELAJARAN ROLE PLAYING DAN KECERDASAN EMOSIONAL SISWA TERHADAP HASIL BELAJAR SIROH - Murtaqiatusholihat Na; Khasanah Khasanah (Akademika : Jurnal Teknologi Pendidikan, 2016)
This study aims to examine: (1) student learning taught by methods Role Playing higher thanstudents taught by lecture method in subjects Siroh. (2) There is an interaction effect between themethods of learning and emotional intelligence of students' learning outcomes in subjects Siroh. (3)Results Learning Siroh students who have high emotional intelligence higher if taught with methodsRole Playing instead of using teaching methods Lecture. (4) Results of learning Siroh the students whohave low emotional intelligence lower than taught methods Role Playing teaching methods LectureThis study used an experimental model. The target population is all students of class IV MIS. AlImaroh West Cikarang Bekasi Regency. Affordable population in this study were students of class IVMIS. Al-Imaroh Cikarang Barat. Samples were taken using sampling, multi-stage random samplingbased group factorial design, so that the selected 40 students.Instruments used to obtain the datathrough the variable learning methods Role Playing (A), emotional intelligence (B), and learningoutcomes Siroh (Y) using a Likert scale. Analysis of the reliability of the variables A and B dab Ycalculated by product Moment, the result of variable A at r table = 0.923, variable B of r table = 0.918and variabek Y of r table = 0.918 Data collection techniques were analyzed using descriptive analysisand inferential analysis such as ANOVA two lanes to test the hypothesis followed by Turkey or Scheffetest. With Liliefors and homogeneity testing using Bartlet test. Statistical tests showed that the data ofthe three variables normal and homogeneous.Results showed that: (1) the results of student learning are taught with methods Role Playinghigher than students taught by lecture method in subjects Siroh. (2) There is an interaction effectbetween the methods of learning and emotional intelligence of students' learning outcomes in subjectsSiroh. (3) Results Learning Siroh students who have high emotional intelligence higher if taught withmethods Role Playing instead of using teaching methods Lecture. (4) Results of learning Siroh thestudents who have low emotional intelligence lower than taught methods Role Playing teachingmethods Lecture.The conclusion of this study is the use of Role Playing pretty effective method to improve learningoutcomes Siroh both the students who have high emotional intelligenc